Higher precipitation strengthens the microbial interactions in semi‐arid grassland soils. Issue 5 (29th January 2018) - Wang, Shang; Wang, Xiaobo; Han, Xingguo; Deng, Ye
Abstract: Aim: Growing attention has been focused on the changes in the structure and diversity of microbial communities under altered precipitation pattern, but little is known about how this factor impacts microbial interactions. Our aim was to elucidate the variations of microbial interactions in semi‐arid grassland soils and determine the key factor in regulating microbial assemblies in water‐limited areas. Location: A c . 3, 700 km transect across three habitats (desert, desert grassland and typical grassland) in Northern China. Time period: July and August 2012. Major taxa studied: Total bacteria and archaea. Method: The random matrix theory (RMT)‐based network inference approach was used to construct species interaction networks. The relationships between microbial network topology and environmental variables were examined by Mantel and partial Mantel tests. Results: At the regional scale (across habitats), mean annual precipitation was the most important factor constraining the network structure, whereas at the local scale (within a habitat), soil conditions and plant parameters became more important, but their relative effects differed among habitats. In particular, no correlation was detected between the desert network and any environmental factors. The number of central species increased substantially in desert grassland and typical grassland networks in comparison to those in the desert network. Inter‐ and intra‐module connections, particularly negative connections, also increased in the two grassland habitats. Main conclusions: Microbial networks become more complex as precipitation increases. A simple network structure (no connectors between modules, more sparsely distributed species and lower competitive links) and less association with environmental factors in the desert network indicate that microbial communities in extremely dry ecosystems are unstable and vulnerable; that is, future climate change will greatly influence microbial interactions in these extremely dry areas. Overall, our findings provide new insight into the way in which microbes respond to changing precipitation patterns by regulating their interactions in water‐limited ecosystems.